Impact of landscape installation design on emotional loneliness: interaction style as a moderating factor - Gong, Mou (Frontiers in Psychology, 2025)
The social isolation measures implemented during the COVID-19 pandemic have exacerbated emotional loneliness, presenting significant challenges in the fields of public health and social psychology. This study examines the potential of landscape design in mitigating emotional loneliness. While prior research indicates that art therapy can reduce environmental loneliness and provides theoretical support for emotion-focused environmental interventions, systematic investigations into the role of landscape installations in alleviating emotional loneliness remain limited. Further exploration of their mechanisms and practical applications is necessary. Through case studies and questionnaire survey-based methods, this research evaluates how design elements—such as cultural references, color application, and function attributes—affect emotional loneliness relief. The findings demonstrate that design elements significantly enhance user interaction (β = 0.339, p < 0.01) and also directly alleviate emotional loneliness (β = 0.258, p < 0.01). User interaction, in turn, exerts a significant direct effect on emotional loneliness relief (β = 0.312, p < 0.01). Mediation analysis confirms that user interaction serves as a partial mediator, with the indirect effect supported by a 95% confidence interval excluding zero (95% CI: 0.065–0.148). Moreover, moderated mediation analysis indicates that interaction style moderates the path from user interaction to emotional loneliness relief. Specifically, the mediation effect is significant at medium and high levels of interaction style (Effect = 0.100–0.161). This study provides theoretical insights into the development of landscape design in relation to emotional health and offers empirical support for the implementation of landscape installations with psychologically supportive functions.